Design of Dual-Band Wearable Crescent-Shaped Button Antenna for WLAN Applications - Ali, S.M. (Springer, 2020)
A new type of a circular polarized crescent-shaped button antenna is proposed for the wireless local area network applications (WLAN). The investigated design is composed of a crescent-shaped antenna. The button disc is located on the top side of a textile material. The design shows dual frequency band like a monopole in 2.5185â2.7206Â GHz, and a broadside pattern in 4.4475â5.3988Â GHz, so that both the off- and on-body communication can be obtained, simultaneously. Another important feature of a wearable antenna is a specific absorption rate (SAR), so that SAR is calculated, which is 0.662Â W/KG for low band and 0.294 for high band, respectively. The SAR is under the limits, according to the health and safety regulations. Therefore, the proposed design is suitable for the body-centric communications. Â© Springer Nature Singapore Pte Ltd. 2020.